Population Dynamics of Hymenia Recurvalis (FAB.) (Amaranth Leaf Webber) in Garhwal Hills of Uttrakhand - Aswal, J. S.; Bisht, B. S. (Indian Journal of Hill Farming, 2018)
In the present study, an attempt has been made to understand the population dynamics ofthe Hymenis recurvalis in different elevations of Garhwal hills. Light traps were installedat three different experimental sites viz. Khadi, (950 m asl) at tropical, Gaza (1450 m asl)at sub-tropical and Ranichauri (1750 m asl) in the temperate region. The pest appearancewas from 27th standard week (first week of July) (1.42-3.90moth/night) up to 46th standardweek (26th November to 2nd December) (1.60-2.0moth/night). first appearance of adultmoths (3.90) were recorded at Khadi (tropical), and Gaza (sub-tropical) (1.42) during 27thstandard week (first week of July) and thereafter, it appeared at Ranichauri (Temperate)(2.0) during the 28th standard week (second week of July). It is clear that the moths firstappeared at lower elevations then spread towards higher elevations. The number of catcheswith highest peak were observed at 24.66 moths/night at Khadi, 30.0 moths/night at Gazaand 17.14 moths/night at Ranichauri during 39th the week (September last week)respectively, which gradually declined after 40th week and sharply declined from 44thweek.